Creating a sustainable vision of nonviolence in schools and society - Singh, Swaranjit; Erbe, Nancy (Advances in religious and cultural studies (ARCS) book series, 2017)
"[This book] is a unique reference source that discusses the value that nonviolent spaces can add to educational institutions and societies. Featuring extensive coverage on relevant topics including conflict skills, intersectional dialogue, mentoring, co-existence, and police brutality, this is an outstanding resource of academic material for educators, academicians, graduate students, and researchers seeking to expand their knowledge on nonviolent methods and techniques for educational environments"--Provided by publisher.